2019
DOI: 10.17759/cpse.2019080301
|View full text |Cite
|
Sign up to set email alerts
|

Internet Use and Depressive Symptoms in Adolescents: a Review

Abstract: The introduction of digital technologies in everyday practices and the reduction of the age of children's access to the Internet creates the need to reflect on the potential benefits and risks associated with digitalization. The article summarizes the main data on the impact of the Internet, in particular social networks, on life satisfaction indicators and symptoms of depression in adolescents. The results of empirical studies conducted in different countries are ambiguous and do not allow to speak about univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
0
2
0
2
Order By: Relevance
“…Due to ambiguity in the results of empirical research regarding the links between psychological well-being and social media use, an approach (Bochaver et al, 2019) that would consider different factors and non-linear relationships between psychological characteristics and features of the digital environment seems promising. In particular, a study that considered the effect of motivational and communicative factors on the relationship between loneliness and the number of online friends found that social networking and compensatory motives increase the desire for openness and online communication, leading to more friends (Hood et al, 2018).…”
Section: Psychological Well-being and The Use Of Social Mediamentioning
confidence: 99%
“…Due to ambiguity in the results of empirical research regarding the links between psychological well-being and social media use, an approach (Bochaver et al, 2019) that would consider different factors and non-linear relationships between psychological characteristics and features of the digital environment seems promising. In particular, a study that considered the effect of motivational and communicative factors on the relationship between loneliness and the number of online friends found that social networking and compensatory motives increase the desire for openness and online communication, leading to more friends (Hood et al, 2018).…”
Section: Psychological Well-being and The Use Of Social Mediamentioning
confidence: 99%
“…Since virtual socialization is currently essential for the development of personality, the study of its multidirectional forms (both positive and negative) is very important and timely (Bogacheva, 2016;Kozyreva & Zverkova, 2017;Shapovalova, 2015;Varaksin, 2016). The appeal to destructive forms of behavior of young people in the virtual space is currently especially relevant in the light of widespread digitalization and informatization (Bochaver et al, 2019;Cherenkov, 2015;Sharov, 2019;Vaisburg, 2019).…”
Section: Problem Statementmentioning
confidence: 99%
“…Чубайс, непосредственно руководивший процессом приватизации, прямо говорит о том, что «… приватизация -это была священная война против коммунистов. А на войне ни денег, ни жертвы не считают» [3]. Он также подчеркивает, что «… приватизация в России до 1997 года вообще не была экономическим процессом.…”
unclassified
“…Она решала совершенно другого масштаба задачи, что мало кто понимал тогда, а уж тем более на Западе. Она решала главную задачу -остановить коммунизм» [3].…”
unclassified